1987
DOI: 10.1159/000153720
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Alpha-l-Antitrypsin and Haptoglobin Phenotypes in Bladder Cancer Patients

Abstract: Frequencies of the α1-antitrypsin (Pi) alleles and haptoglobin phenotypes have been determined in a series of 264 North-German patients with bladder cancer. Compared to a healthy control population, we found a statistically significant decrease of Hp 2-2 phenotype in the patient series. A significant increase of the serum Pi Z allele, as previously shown for patient groups with certain other tumours, could also be confirmed for bladder cancer. Furthermore, a distinct association between a lowered M … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 10 publications
0
30
0
Order By: Relevance
“…Furthermore, Dunzendorfer et al (1980) found increased serum haptoglobin levels in patients with urogenital tumors. Only haptoglobin phenotype has been examined in patients with bladder cancer, as observed in a study by Benkmann et al (1987). They discovered that a certain haptoglobin phenotype was found at significantly lower levels in patients with bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Dunzendorfer et al (1980) found increased serum haptoglobin levels in patients with urogenital tumors. Only haptoglobin phenotype has been examined in patients with bladder cancer, as observed in a study by Benkmann et al (1987). They discovered that a certain haptoglobin phenotype was found at significantly lower levels in patients with bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The haptoglobin phenotype in patients with bladder cancer was reported in a study by Benkmann et al (1987). However, to the best of our knowledge, serum haptoglobin levels have not been evaluated in patients with bladder cancer.…”
Section: Introductionmentioning
confidence: 93%
“…11,14) It is produced in the liver and immunological cells and secreted into serum. Its level changes in the serum in response to infection, inflammation, and various malignant diseases, including lung and bladder cancer, 15,16) leukemia, 17) breast cancer, 18) malignant lymphoma, 19) urogenital tumors, 20) and esophageal squamous cell carcinoma. 21) Of these 41 genes, we especially observed Hp gene.…”
Section: Haptoglobin Proved a Prognostic Biomarker In Peripheral Bloomentioning
confidence: 99%
“…In humans, the HP locus is polymorphic, with two codominant alleles (HP1 and HP2) that yield three distinct genotypes/phenotypes (Hp1-1, Hp2-1 and Hp2-2) (Sadrzadeh and Bozorgmehr, 2004). Elevated levels of haptoglobin have been demonstrated in lung cancer (Beckman et al, 1986), bladder cancer (Benkmann et al, 1987), leukemia (Mitchell et al, 1988), breast cancer (Awadallah and Atoum, 2004), malignant lymphoma (Epelbaum et al, 1998), urogenital tumors (Dunzendorfer et al, 1980), esophageal squamous cell carcinoma , ovarian cancer (Zhao et al, 2007) and gliomas (Kumar et al, 2010).…”
Section: Elevated Serum Haptoglobin Is Associated With Clinical Outcomentioning
confidence: 99%